Transition to a Low-Emissions Economy in Poland - World Bank (Washington, DC, 2017)
Against the backdrop of agreement that global coordinated action is needed to prevent dangerous climate change, individual countries are thinking through the implications of climate action for their economies and people. The rest of the report is organized along the following lines. The next section provides background on Poland's greenhouse gas (GHG) emissions. Then section B sets out Poland's existing carbon abatement targets and key policy challenges related to GHG mitigation. The next section summarizes the innovative methodological approach used by the report. Section D discusses the methods and implications of constructing business-as-usual or reference scenarios. Section E provides the major findings from the first model, the engineering approach, on the costs of measures aimed at GHG mitigation for Poland. Section F explains how these findings are expanded and revised by incorporation into the first macroeconomic model. Section G provides an analysis of the economic impact through 2020 of mitigation measures within the constraints of European Union (EU) policy arrangements. Section H examines the energy sector and how Section E's findings are enhanced by optimization of the structure of the energy sector. Section I takes a first look at the challenges of energy efficiency. Section J provides additional analysis of the transport sector. The last section provides some notes on additional issues and further work.